Real-time facial expression recognitions: A review - Adeshina, Adekunle Micheal; Lau, Siong Hoe; Loo, Chu Kiong (IEEE, 2009)
With the unambiguous statement on the importance of facial configuration for the judgments of human emotion, facial expression recognition has been the utmost research in affective computing in the recent years. The motive is to empower computer so that it could be adaptive to extracting and classifying various user emotions into the "universal facial expressions" or its subsets. This paper reviews a number of methodological approaches relative to real-time facial expression recognitions systems and proposes further research areas that require more attention towards the successful implementation of a more efficient channel for machine - emotion interaction.